ON THE 2019 BOOKER PRIZE. - MOSELEY, MERRITT (Sewanee Review)
The article announces the nominees for 2019 Booker Prize, including "The Testaments" by Margaret Atwood, "Ducks, Newburyport" by Lucy Ellmann, and "Quichotte" by Salman Rushdie.